Natural transmission of dengue virus by aedes albopictus at Monterrey, Northeastern Mexico - Sánchez Rodríguez, Olga Saraí; Sánchez Casas, Rosa María; Laguna Aguilar, Maricela; Alvarado Moreno, Marcela Selene; Zárate Nahón, Erwy Arvid; Ramírez Jiménez, Rocío; Medina de la Garza, Carlos Eduardo; Torres Zapata, Raúl; Domínguez Galera, Marco Antonio; Mis Ávila, Pedro; Fernández Salas, Ildefonso (Southwestern Entomologist, 2014)
Dengue cases occur frequently at Nuevo Leon, Mexico, where Aedes aegypti (L.) and Ae. albopictus (Skuse) are present. Ae. albopictus is considered the second vector of dengue. Because it bites humans outdoors during the day, the mosquito plays an important role in transmission of dengue virus (DENV). However, no previous studies at Nuevo Leon indicated the role of the mosquito outdoors. To assess Ae. albopictus for dengue virus, mosquitoes were collected from April to October 2010 at five localities at Guadalupe and Santiago, Nuevo Leon, (Northeast) Mexico, by using two methods: engine backpack aspirator and ovitraps. In total, 1,836 Ae. albopictus and 833 Ae. aegypti mosquitoes were collected by ovitrap and engine backpack aspirator methods. Groups of mosquitoes were processed by RT-PCR. Examination for DENV infection of mosquitoes showed one positive group of four female Ae. albopictus from an ovitrap. This research provided information that showed transovarial transmission of dengue virus in Ae. albopictus occurred naturally, maintaining endemic levels of disease at a study site.